UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI PEMBINAAN DAN PENDAMPINGAN DI SMA NEGERI 2 TEBO - EDI WIDODO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve teacher competence in preparing lesson plans (RPP) through coaching and mentoring at SMA Negeri 2 Tebo for the 2019/2020 school year. The type of research conducted is School Action Research (PTS). This School Action Research aims to improve the competency and performance of subject teachers in preparing lesson plans (RPP) through coaching and mentoring at SMA Negeri 2 Tebo, Tebo Regency, Jambi Province, semester I for the 2019/2020 academic year. This School Action Research uses a cyclical strategy or approach with the following steps: planning, implementing, observing and reflecting. The results showed that there was an increase in the competence of teachers in preparing lesson plans as follows: Teacher competency in preparing lesson plans in the initial conditions, the average value was 67.37 and the percentage of eligibility was 41.30%. At the end of the first cycle the score became 77.6 with a feasibility percentage of 82.61%. At the end of the second cycle, the average value obtained was 81.39, the percentage of eligibility was 100% and the total increase was 2.17%. Another achievement from the results of this study is the shift in the teacher's way of thinking from being completely bureaucratic, instructive and highly dependent on the work of others to non-bureaucratic, cooperative, collaborative, creative, and independent. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kompetensi guru dalam menyusun rencana pelaksanaan pembelajaran (RPP) melalui pembinaan dan pendampingan di SMA Negeri 2 Tebo tahun pelajaran 2019/2020. Jenis penelitian yang dilakukan adalah Penelitian Tindakan Sekolah (PTS). Penelitian Tindakan Sekolah ini bertujuan untuk untuk meningkatkan Kompetensi dan kinerja Guru Mata Pelajaran dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) melalui pembinaan dan pendampingan di SMA Negeri 2 Tebo Kabupaten Tebo Provinsi Jambi semester I Tahun pelajaran 2019/2020. Penelitian Tindakan Sekolah ini menggunakan strategi atau pendekatan siklus dengan langkah-langkah: perencanaan, pelaksanaan, observasi (pengamatan) dan refleksi. Hasil penelitian menunjukkan adanya peningkatan kompetensi guru menyusun RPP sebagai berikut: Kompetensi guru menyusun RPP pada kondisi awal nilai rata-rata 67,37 dan prosentase kelayakan 41,30%. Pada akhir siklus I nilai menjadi 77,6 dengan prosentase kelayakan 82,61%. Akhir siklus II nilai yang diperoleh rata-rata 81,39, prosentase kelayakan 100% serta total kenaikan mencapai 2,17%. Prestasi yang lain dari hasil penelitian ini adalah terjadinya pergeseran cara berfikir guru dari serba birokratik, instruktif dan ketergantungan tinggi pada hasil karya orang lain ke non birokratik, kooperatif, kolaboratif, kreatif, dan mandiri.